Synthesis and Structure of Ionic Liquids Containing the [Al(OC6H4CN)4]– Anion1. Issue 5 (26th March 2013) - Lund, Henrik; Harloff, Jörg; Schulz, Axel; Villinger, Alexander
Abstract The synthesis, structure, and physical properties of ionic liquids (IL) bearing the novel [Al(O–C6H4–CN)4]– ion as counterion to the commonly used [NR4]+, [PR4]+ and imidazolium ions are reported. Both the influence of the alkyl chain length as well as the functionalization with cyano groups is studied. These ILs are easily obtained by reaction of Ag[Al(O–C6H4–CN)4] with the corresponding ammonium, phosphonium, and imidazolium halides. The stability towards electrophilic cations was investigated. All prepared salts have a window for the liquid phase of ca. 200 °C and are thermally stable up to 450 °C. The solid‐state structures reveal only weak cation···anion and anion···anion interactions in accord with the observed low melting points (glass transition points).